Strategi Komunikasi Orang dengan Hiv Aids (Odha) Menghadapi Stigma Masyarakat - Riniwaty Makmur (LUGAS Jurnal Komunikasi, 2017)
Results of various researches about people with HIV AIDS (ODHA) concluded that in general, stigma happens to ODHA. Stigma has been a basis for discrimination against ODHA and becoming obstacle in many efforts to overcome impact of HIV AIDS. This research uses the qualitative approach and the data was collected through interview, document review, including discussion found in specific websites used by ODHA support group. The research uncovered that ODHA has been stigmatized by a range of group such as family, school, and religious leader.  In dealing with stigma, some of ODHAs prefer to keep their status in secret, in order to protect themselves and their family, and some others choose to be straightforward about their condition. The decision on what strategy to take, significantly depends on support they receive from family and their significant others.